2017
DOI: 10.1051/0004-6361/201730897
|View full text |Cite
|
Sign up to set email alerts
|

Young, metal-enriched cores in early-type dwarf galaxies in the Virgo cluster based on colour gradients

Abstract: Early-type dwarf galaxies are not simply featureless, old objects, but were found to be much more diverse, hosting substructures and a variety of stellar population properties. To explore the stellar content of faint early-type galaxies, and to investigate in particular those with recent central star formation, we study colours and colour gradients within one effective radius in optical (g − r) and near-infrared (i − H) bands for 120 Virgo cluster early-type galaxies with −19 mag < M r < −16 mag. Twelve galaxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 91 publications
0
26
0
Order By: Relevance
“…As an observable signature that should be studied those cluster dEs should show a negative vertical stellar age gradient and a positive blue colour gradient or at least flat ones, as well as a radially increasing stellar velocity dispersion. This effect might already be indicated by a few dEs in the Coma cluster with radial changes in age (Koleva et al 2011) and by the negative or flat age gradients derived in a few Virgo cluster dEs (Urich et al 2017) from the SMAKCED sample (Janz et al 2012).…”
Section: Dwarf Galaxy Transformation and Stellar Population Gradientsmentioning
confidence: 85%
“…As an observable signature that should be studied those cluster dEs should show a negative vertical stellar age gradient and a positive blue colour gradient or at least flat ones, as well as a radially increasing stellar velocity dispersion. This effect might already be indicated by a few dEs in the Coma cluster with radial changes in age (Koleva et al 2011) and by the negative or flat age gradients derived in a few Virgo cluster dEs (Urich et al 2017) from the SMAKCED sample (Janz et al 2012).…”
Section: Dwarf Galaxy Transformation and Stellar Population Gradientsmentioning
confidence: 85%
“…These latter authors suggested that galaxy harassment is less effective in clusters like Virgo, given their large velocity dispersion, and more efficient in group environments (Yozin & Bekki 2015). Urich et al (2017) claimed that the ram pressure stripping is therefore more likely to explain their blue-core dEs in the Virgo cluster. According to the model of Vollmer (2009), ram pressure stripping has a hard time in removing the gas from the center of the galaxies and it can even raise the star formation rate in the cores (Kronberger et al 2008).…”
Section: Comparison Between the Clusters And Possible Formation Scenamentioning
confidence: 99%
“…Given the known stellar population diversity of Virgo cluster early-type dwarfs (Michielsen et al 2008;Kim et al 2010), we examine whether there are systematic differences between the phase-space regions. The recent optical -near-infrared photometric study of Urich et al (2017) provides us with colors and color gradients for 119 Virgo early-type dwarfs. Urich et al defined an age-sensitive and a metallicity-sensitive color by combining g, r, i, and H bands into linear combinations that lead to a nearly orthogonal age-metallicity grid for simple stellar populations.…”
Section: Observational Findingsmentioning
confidence: 99%